2019
DOI: 10.1590/fst.27417
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pH and color in pork meat using VIS-NIR Near-infrared Spectroscopy (NIRS)

Abstract: The potential of near-infrared spectroscopy (NORS) to predict the physicochemical characteristics of the porcine longissimus dorsi (LD) muscle was evaluated in comparison to the standard methods of pH and color for meat quality analysis compared to the pH results with Colorimeter and pH meter. Spectral information from each sample (n = 77) was obtained as the average of 32 successive scans acquired over a spectral range from 400 -2498 nm with a 2 -nm gap for calibration and validation models. Partial least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…However, in the case of redness a*, yellowness b*, and CL muscle in each day of aging, CV ranges were 11.38–15.44, 12.44–14.76, and 13.02–16.41 respectively. The value of the CV indicates that the data can guarantee significant calibration [ 34 ]. According to Andrés, [ 35 ], the acceptable CV level should be no less than 20%, while De Marchi [ 25 ] claims that a range of CV 6%–19% for color index indicates the existence of exploitable variability in developing calibration models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of redness a*, yellowness b*, and CL muscle in each day of aging, CV ranges were 11.38–15.44, 12.44–14.76, and 13.02–16.41 respectively. The value of the CV indicates that the data can guarantee significant calibration [ 34 ]. According to Andrés, [ 35 ], the acceptable CV level should be no less than 20%, while De Marchi [ 25 ] claims that a range of CV 6%–19% for color index indicates the existence of exploitable variability in developing calibration models.…”
Section: Resultsmentioning
confidence: 99%
“…In the internal full cross-validation process, the prediction capability of the model was evaluated, using the coefficient of determination in calibration (R 2 c ), standard error of calibration (SEC), coefficient of determination in prediction (R 2 p ), and standard error of prediction (SEP). Moreover, the prediction models were evaluated using the residual prediction deviation (RPD = SD/SEP) [ 34 ]. An RPD value above 3 is considered adequate for routine analysis, between 2 to 3 represents a good prediction, and less than 1.5 indicates incorrect prediction and the model cannot be used for prediction [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Further, both NIRS and Raman spectroscopy are used to predict meat quality based on the chemical composition of the products. Furtado et al (2018) found that NIRS was able to predict color in pork when measured at 24 hr postmortem. However, spectroscopy methods still have inconsistencies in their ability to measure other meat quality characteristics such as tenderness.…”
Section: Marketing Pork Based On Qualitymentioning
confidence: 97%
“…11 The PH value and color of pork change with the deterioration of pork. 12 It is worth mentioning that these changes can be identified from near-infrared spectroscopy. For example, Douglas F. Barbin et al evaluated microbial contamination in pork through hyperspectral technology.…”
Section: Introductionmentioning
confidence: 99%